MICROBIOLOGICAL CONTROL OF GOAT MILK FROM SIBIU AREA REGARDING THE HYGIENE ASSURANCE AND FOOD SAFETY - LETIŢIA OPREAN; Ş. BAHCIVANGI; RAMONA IANCU (Scientific Papers Animal Science and Biotechnologies, 2023)
The main objective concerning food safety is touching the highest possible degree of protection for human health and consumers interests regarding the food. Because of that, we analyze goat milk from three different county and the tests were performed searching the Salmonella presence. In our tests we detect an insignificant presence of Salmonella but this microorganism can be eliminated by specific methods so the food safety will be ensured.